(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article presents the results of a blood glucose test in heifers and cows of different ages, depending on the periods of pregnancy, lactation, type of feeding, as well as soil, climatic and environmental conditions of the region. The time of the most pronounced disorders of carbohydrate metabolism in cows has been established. The parameters of carbohydrate metabolism characteristic of healthy and sick cows with impaired carbohydrate metabolism under conditions of silage-concentrate and hay-concentrate types of feeding have been established.